The Impact of Hyponatremia on the Severity of Childhood Tuberculous Meningitis - Salih, Rashid; Toorn, Ronald van; Seddon, James A.; Solomons, Regan S. (Frontiers in Neurology, 2022)
Introduction: Hyponatremia and/or hypoglycorrhachia are commonly encountered biochemical derangements during the acute stage of childhood tuberculous meningitis (TBM). Few studies have explored the correlation between these derangements and the staging of TBM disease (severity), or explored their role as biomarkers for vascular ischemic events, hydrocephalus, or seizures. Methods: We aimed to identify the prevalence and the correlation between serum hyponatremia (mild, moderate and severe) and/or hypoglycorrhachia in relation to clinical TBM features such as stage of disease, seizures and stroke in children diagnosed with definite and probable TBM, between 1985 and 2015, at Tygerberg Hospital, Cape town, South Africa. Results: The prevalence of hyponatremia was 344 out of 481 (71.5%) patients; 169 (49.1%) had mild hyponatremia, 146 (42.4%) moderate hyponatremia and 29 (8.4%) severe hyponatremia. Children with severe hyponatremia had higher frequency of stroke [odds ratio (OR) 4.36, 95% confidence interval (CI) 1.24–15.35; p = 0.01], brainstem dysfunction (OR 7.37, 95% CI 2.92–18.61; p < 0.01), cranial nerve palsies (OR 2.48, 95% CI 1.04–5.91; p = 0.04) and non-communicating hydrocephalus (OR 2.66, 95% CI 1.09–6.44; p = 0.03). Children with moderate hyponatremia and mild hyponatremia compared to those without hyponatremia similarly were more likely to exhibit signs of brainstem dysfunction (OR 1.91, 95% CI 1.11–3.28; p = 0.02) and hydrocephalus (OR 3.18, 95% CI 1.25–8.09; p = 0.01), respectively. On multivariable analysis only brainstem dysfunction was significantly associated with severe hyponatremia [adjusted odds ratio (aOR) 4.46, 95% CI 1.62–12.30; p < 0.01]. Children with hypoglycorrhachia compared to normoglycorrhachia were more likely to have had longer symptom duration prior to admission (OR 1.87, 95% CI 1.09–3.20; p = 0.02), non-communicating hydrocephalus (OR 1.64, 95% CI 0.99–2.71; p = 0.05), higher cerebrospinal white cell counts (OR 3.00, 95% CI 1.47–6.12; p < 0.01) and higher CSF protein concentrations (OR 2.51, 95% CI 1.49–4.20; p < 0.01). On multivariable analysis raised CSF protein concentration >1 g/L was significantly associated with hypoglycorrhachia (aOR 2.52, 95% CI 1.44–4.40; p < 0.01). Death rates did not differ by sodium level category or presence of hypoglycorrachia, however an increasing trend of children that had demised was noted the more severe the sodium category. Conclusion: Hyponatremia and/or hypoglycorrhachia occur in more than two-thirds of children with TBM. Severe TBM disease complications such as brainstem dysfunction was associated with moderate hyponatremia, while severe hyponatremia was associated with brainstem dysfunction, stroke, cranial nerve palsies and non-communicating hydrocephalus. Cerebrospinal fluid (CSF) glucose depletion correlated with non-communicating hydrocephalus and increased CSF inflammation.